Antimicrobial activity of the ethanolic extract of Coleus aromaticus against common wound pathogens - Muniandy K.; Hassan Z.; Mohd Hafez Mohd Isa (Research Journal of Pharmaceutical, Biological and Chemical Sciences, 2024)
Indexed by Scopus